Photon counting x‐ray imaging with K‐edge filtered x‐rays: A simulation study. Issue 3 (24th February 2016) - Atak, Haluk; Shikhaliev, Polad M.
Abstract : Purpose: In photon counting (PC) x‐ray imaging and computed tomography (CT), the broad x‐ray spectrum can be split into two parts using an x‐ray filter with appropriate K ‐edge energy, which can improve material decomposition. Recent experimental study has demonstrated substantial improvement in material decomposition with PC CT when K ‐edge filtered x‐rays were used. The purpose of the current work was to conduct further investigations of the K ‐edge filtration method using comprehensive simulation studies. Methods: The study was performed in the following aspects: (1) optimization of the K ‐edge filter for a particular imaging configuration, (2) effects of the K ‐edge filter parameters on material decomposition, (3) trade‐off between the energy bin separation, tube load, and beam quality with K ‐edge filter, (4) image quality of general (unsubtracted) images when a K ‐edge filter is used to improve dual energy (DE) subtracted images, and (5) improvements with K ‐edge filtered x‐rays when PC detector has limited energy resolution. The PC x‐ray images of soft tissue phantoms with 15 and 30 cm thicknesses including iodine, CaCO3, and soft tissue contrast materials, were simulated. The signal to noise ratio (SNR) of the contrast elements was determined in general and material‐decomposed images using K ‐edge filters with different atomic numbers and thicknesses. The effect of the filter atomic number and filter thickness on energy separation factor and SNR was determined. The boundary conditions for the tube load and halfvalue layer were determined when the K ‐edge filters are used. The material‐decomposed images were also simulated using PC detector with limited energy resolution, and improvements with K ‐edge filtered x‐rays were quantified. Results: The K ‐edge filters with atomic numbers from 56 to 71 and K ‐edge energies 37.4–63.4 keV, respectively, can be used for tube voltages from 60 to 150 kVp, respectively. For a particular tube voltage of 120 kVp, the Gd and Ho were the optimal filter materials to achieve highest SNR. For a particular K ‐edge filter of Gd and tube voltage of 120 kVp, the filter thickness 0.6 mm provided maximum SNR for considered imaging applications. While K ‐edge filtration improved SNR of CaCO3 and iodine by 41% and 36%, respectively, in DE subtracted images, it did not deteriorate SNR in general images. For x‐ray imaging with nonideal PC detector, the positive effect of the K ‐edge filter was increased when FWHM energy resolution was degraded, and maximum improvement was at 60% FWHM. Conclusions: This study has shown that K ‐edge filtered x‐rays can provide substantial improvements of material selective PC x‐ray and CT imaging for nearly all imaging applications using 60–150 kVp tube voltages. Potential limitations such as tube load, beam hardening, and availability of filter material were shown to not be critical.